MAHAR PERNIKAHAN MENGGUNAKAN SAHAM SEBAGAI PERKEMBANGAN HUKUM ISLAM: KOMPARASI PERSPEKTIF IMAM SYAFI’I DAN IMAM QUDURI - Mustakim, Ahmad; Muda'i, Syaiful; Hakim, Lukman (USRATUNA: Jurnal Hukum Keluarga Islam, 2024)
The dowry (mahr) is a consequence of the marriage contract, traditionally given in various forms, such as property, teaching Qur'an, or other valuable contributions. However, societal dynamics have introduced new forms, including shares as dowry. This study explores the legality and minimum value of shares as dowry according to Imam Shafi'i and Imam Quduri. The research employs a qualitative library study with primary sources including al-Umm by Imam Shafi'i and al-Quduri by Imam Quduri, and secondary sources such as Bidayatul Mujtahid and Roudhatut Thalibin. Data is collected through documentation and analyzed using content analysis. Imam Quduri considers shares valid as dowry, setting a minimum value of ten dirhams (approximately Rp. 42,494.29). If the shares are below this amount, the dowry is invalid and must be replaced with a mahr mithil (customary dowry). He emphasizes preserving the dignity of the bride. Imam Shafi'i, referencing Surah al-Baqarah (2:237) and relevant hadiths, adopts a more flexible stance, allowing shares as dowry without specifying a minimum value. Both scholars base their views on the Qur'an and Hadith but differ in interpretation, reflecting a textualist approach. This study highlights the evolving understanding of dowry in Islamic jurisprudence.